Peramalan Kinerja Keuangan PT Bank Syariah Bukopin Menggunakan Metode ARIMA Box-Jenkin - Irmatul Hasanah (Banque Syar'i : Jurnal llmiah Perbankan Syariah, 2022)
Public trust in banks can be influenced by the performance of a bank which can be seen from its profitability ratios. A decrease in the performance of a bank will lead to a decrease in the level of profitability of a bank. So that if there is a decrease in the level of profitability will cause a decrease in public trust in the bank. This study aims to predict the financial performance data of PT Bank Syariah Bukopin using the ARIMA Box-Jenkins method. The data used for this research is quarterly profitability ratio data for ROA and ROE for 2010-2020. This results shows that ARIMA(1,1,0) model can be used to find the value of ROA in th